PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS KINERJA GURU DI MTs SE KECAMATAN RAMBAH KABUPATEN ROKAN HULU - -, Nurbaini; Afifah, Nurul; Brahmana, Eti Meirina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aim of this study was analyzing the headmasterâs roles in increasing the quality of teaches performace in MTs in sub-district Rambah, Rokan Hulu regency. This study has been conducted on Desember 2014 to January 2015. The samples were 3 headmasters. The research instruments are using inquiry method and analyzing descriptively. Result showed 71.3% of the headmastersâ roles in increasing the quality of teachersâ performance in MTs especially in sub-district Rambah, Rokan Hulu regency. It can be concluded that the roles of headmasters in improving teachers performance quality at MTs in sub-district Rambah, Rokan Hulu regency was in good category.